2013
DOI: 10.15218/zjms.2013.0047
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hyoscine N– butyl bromide on the duration of active phase of labor

Abstract: Background and objective: Hyoscine N-butyl bromide acts by inhibiting cholinergic transmission in pelvic parasympathetic ganglia and antagonizing muscarinic receptors of smooth muscles in the abdomen and pelvic organs, thus relieving spasm aiding to cervical dilation. This study is to assess the efficacy of Hyoscine butyl bromide on cervical dilation in multigravid pregnant women during the active phase of labor. Methods: A randomized clinical prospective trial was conducted in maternity hospital in Sulaimaniy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…Eleven studies were excluded because of study design was different from our inclusion criteria and seven studies were excluded because of their comparators were different from the inclusion criteria of this review. In the search update on December 2nd 2019 four other studies were found [30][31][32][33] . Finally, 20 studies were included in the meta-analysis ( Fig.…”
Section: Literature Searchmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies were excluded because of study design was different from our inclusion criteria and seven studies were excluded because of their comparators were different from the inclusion criteria of this review. In the search update on December 2nd 2019 four other studies were found [30][31][32][33] . Finally, 20 studies were included in the meta-analysis ( Fig.…”
Section: Literature Searchmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. Six of the studies were conducted in Iran [19][20][21][22][23]35]; three in Egypt [16,18,36]; three in Nigeria [17,24,32]; two in Iraq [30,31] and one in each following countries: Saudi Arabia [34], West Indies Jamaica [14], Mexico [25], Turkey [10], Puducherry [33] and Pakistan [15]. All studies were performed in the hospital setting, mostly in university hospitals.…”
Section: Characteristics and Quality Assessment Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations